Impact of an MHD Cattaneo-Christov model for a Williamson fluid flow across a wedge with a convective boundary condition: Homotopy Analysis Method. Issue 1 (31st December 2023) - Mallikarjun, P.; Umadevi, K. B.
Abstract : The present study aims to scrutinise the influence of the Cattaneo-Christov (CC) heat flux model on magnetohydrodynamic (MHD) laminar boundary-layer flow through a wedge in a non-Newtonian Williamson fluid along with convective boundary condition embedded in a porous medium. Significantly, the presence of the CC model explores the heat transfer characteristics which forecast the effect of thermal relaxation time on the boundary-layer phenomenon. The governing equations are formulated and modified into non-linear, coupled ODEs by utilising similarity transformations and then tackled by Homotopy Analysis Method (HAM). The obtained results are discussed and presented graphically for various values of emerging parameters on velocity and temperature distributions. The results reveal that the velocity is an enhancing function of the magnetic parameter, permeability parameter and Hartree pressure gradient parameter whereas decreasing with larger values of the Williamson fluid parameter. It is evident that the temperature upsurges due to the Biot number and decays with the relaxation parameter. The numerical values of skin-friction and Nusselt number are tabulated. Comparative reviews between the formerly published literature and the current data are made for specific cases, which are inspected to be in tremendous agreement. Abbreviations: BLF: Boundary layer flow; MHD Magnetohydrodynamic; CC model: Cattaneo-Christov model; NNF: non-Newtonian fluid; ODEs: Ordinary differential equations; PDEs: Partial differential equations